Effect of veneering material on the deformation suffered by implant-supported fixed prosthesis framework - Grando, Antônio Francisco; Rezende, Carlos Eduardo Edwards; Sousa, Edson Antonio Capello [UNESP]; Rubo, José Henrique (FapUNIFESP (SciELO), 2014)
The aim of this study was to evaluate the deformation suffered by cantilevered implant-supported fixed prostheses frameworks cast in silver-palladium alloy and coated with two occlusal veneering materials: acrylic resin or porcelain. Material and Methods: Two strain gauges were bonded to the inferior surface of the silver-palladium framework and two other were bonded to the occlusal surface of the prosthesis framework covered with ceramic and acrylic resin on each of its two halves. The framework was fixed to a metallic master model and a 35.2 N compression force was applied to the cantilever at 10, 15 and 20 mm from the most distal implant. The measurements of deformation by compression and tension were obtained. The statistical 2-way ANOVA test was used for individual analysis of the experiment variables and the Tukey test was used for the interrelation between all the variables (material and distance of force application). Results: The results showed that both variables had influence on the studied factors (deformation by compression and tension). Conclusion: The ceramic coating provided greater rigidity to the assembly and therefore less distortion compared with the uncoated framework and with the resin-coated framework. The cantilever arm length also influenced the prosthesis rigidity, causing higher deformation the farther the load was applied from the last implant.
Keywords: Dental implants; Dental prosthesis design; Dental veneers; Implant-supported dental prosthesis